Archéologie du bâti et archéométrie au Mont-Saint-Michel, nouvelles approches de Notre-Dame-sous-Terre - Christian Sapin; Maylis Baylé; Stéphane Büttner; Pierre Guibert; Sophie Blain; Philippe Lanos; Annick Chauvin; Philippe Dufresne; Christine Oberlin (Archéologie Médiévale)
Collective analysis of several archeometric disciplines, used for the first time within the framework of a CNRS programme, has resulted in a new approach – orientated around standing building studies – to the study of Notre-Dame-sous-Terre, at Mont-Saint-Michel. The chronology for the edification of the architectural elements has been defined by dating the mortars and charcoal, bricks or ceramic building materials, by 14C, thermoluminescence and magnetic dating. These analyses, preceded by a documentary study, archaeological analysis of the elevations and new surveys, indicate dates spanning the 10th century, and tend to show that there were two successive masonry blocks.